Does gamification work in a serious context? The influence of gamification, utilitarian, and hedonic features in the community-based crowdfunding platform - Nur Aqilah Hazirah Mohd Anim; Nor Asiah Omar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Crowdfunding can provide financial aid to the underserved in a fast and safe manner. With the diffusion of technology, more people have relied on online crowdfunding platforms to fund their projects. However, researchers have found that contributors’ willingness to support the projects on crowdfunding platforms financially has been on the decline. This study aimed to investigate the ability of crowdfunding platform features to influence the intentions of potential contributors to donate on the platform. This research proposed three variables based on economic utility theory, flow theory, and persuasive theory: utilitarian features; hedonic features; and gamification features. Due to the nascent stage of the crowdfunding environment in Malaysia, this study managed to collect 176 valid responses through virtual snowball sampling method. SPSS was employed to test the three hypotheses. The empirical findings reveal that utilitarian features were the most crucial factor in driving contributors’ intention to participate in a crowdfunding project. Hedonic and gamification features, on the other hand, do not directly influence contributors’ behavior. Theoretically, this study enriches the literature on human-computer interaction by examining the role of the crowdfunding platform to attract potential contributors and enhances the understanding of the implementation of gamification in the crowdfunding platform. Finally, this research suggests that future studies should conduct research that specifically involves advanced game-like settings to investigate the real potential of gamification in crowdfunding activities.